Pengaruh Amicus Curiae (Sahabat Pengadilan) dalam Mempengaruhi Putusan Hakim menurut Sistem Peradilan Pidana - Yudha Prawira Ramadhan; Nandang Sambas (Bandung Conference Series: Law Studies, 2024)
Abstract. This research focuses on the regulation of Amicus Curiae in criminal procedural law in Indonesia and the influence of Amicus Curiae on judges' decisions in criminal justice in Indonesia. This research method is normative juridical. The results of this research are that amricus curiae has not been regulated explicitly and clearly in the Indonesian Criminal Procedure Law. However, there are several regulations that serve as the basis for allowing the use of amricus curiae in Indonesian criminal procedural law, including the provisions of Article 5 paragraph (1) of Law Number 48 of 2009 concerning Judicial Power, Article 14 of Constitutional Court Regulation Number 06/PMK/2005, and Article 180 paragraph (1) Law Number 8 of 1981 concerning the Criminal Procedure Code. Amicus curiae influences judges' decisions in Indonesia as material for consideration. Although amicus curiae does not guarantee a lighter sentence for the defendant, its existence clearly has an influence and is considered by the judge as a factor in the decision-making process. Abstrak. Penelitian ini berfokus pada pengaturan Amicus Curiae dalam hukum acara pidana di Indonesia dan pengaruh Amicus Curiae terhadap putusan hakim dalam peradilan pidana di Indonesia. Metode penelitian ini yuridis normatif. Hasil penelitian ini amricus curiae belum diatur secara eksplisit dan jelas dalam Hukum Acara Pidana Indonesia. Meskipun demikian terdapat beberapa pengaturan yang dijadikan dasar diperbolehkannya penggunaan amricus curiae dalam hukum acara pidana Indonesia diantaranya ketentuan Pasal 5 ayat (1) Undang-Undang Nomor 48 Tahun 2009 tentang Kekuasaan Kehakiman, Pasal 14 Peraturan Mahkamah Konstitusi Nomor 06/PMK/2005, dan Pasal 180 ayat (1) Undang-Undang Nomor 8 Tahun 1981 Tentang Kitab Undang-Undang Hukum Acara Pidana. Amicus curiae berpengaruh terhadap putusan hakim di Indonesia sebagai bahan pertimbangan. Meskipun amicus curiae tidak menjamin vonis terdakwa menjadi lebih ringan, keberadaannya jelas berpengaruh dan dipertimbangkan oleh hakim sebagai salah satu faktor dalam proses pengambilan keputusan.